Application of Cart Method in Analyzing Factors Affecting Nutritional Status of Children Aged 6-23 Months - Izzati Rahmi; Yozza Hazmira; Husna Radhiatul; Rahmy Hafifatul Auliya (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2021)
This study aims to analyze factors that affect the nutritional status of children aged 6-23 months. The data used were acquired from a survey conducted at mother and child health services (‘posyandu’), daycares, and households in four districts in Padang City, West Sumatera. In this study, variables that are hypothesized to contribute to nutritional status are sex, birth weight, family income, number of family dependents, exclusive breastfeeding status, mother's employment status, education level, knowledge and nutritional behavior. Data analysis was done by using tree structure analysis namely CART method. It is showed that variables which significantly affect the nutritional status of children aged 6-23 months are mother’s education level, knowledge and nutritional behavior. Children with low mother’s education level have higher prevalence of severely underweight and underweight when mother’s knowledge is poor or enough. in the group of children whose mothers have higher level of education, the variable that has a significant influence on child’s nutritional status is mother's nutritional behavior. In the group of children whose mothers have higher level of education, the variable that has a significant influence on child’s nutritional status is mother's nutritional behavior, the prevalence of overweight is likely to be high in children whose mothers nutritional behaviour is not good. Therefore, intervention from related parties is needed to implement programs for improving mother's knowledge about nutrition that will lead to better child’s nutritional status.